Effect of training leading to repetition failure on muscular strength: A systematic review and meta-analysis - Davies, T.; Orr, R.; Halaki, M.; Hackett, D. (Sports Medicine, 2016)
It remains unclear whether repetitions leading to failure (failure training) or not leading to failure (non-failure training) lead to superior muscular strength gains during resistance exercise. Failure training may provide the stimulus needed to enhance muscular strength development. However, it is argued that non-failure training leads to similar increases in muscular strength without the need for high levels of discomfort and physical effort, which are associated with failure training.